Genadz Apanasavich Tsykhun (10/30/1936 – 10/18/2024) - Morozova, Nadežda (Slavistica Vilnensis, 2025)
Henadz Apanasavich Tsykhun, one of the most famous Belarusian linguists, Doctor of Philology (1982), Professor (1996), Chief Researcher at the Yakub Kolas Institute of Linguistics of the National Academy of Sciences of Belarus, Vice-President of the International Eurasian Academy of Sciences (1994–1995), Vice-President of the International Association of Belarusianists (1994–2000), died on October 18, 2024. The editors of the journal Slavistica Vilnensis expresses sincere condolences to the family and friends of the professor, his many students and colleagues.
Keywords: Genadz Tsykhun; Belarusian linguists; Slavic studies